Managing sleep disturbances in children with atopic dermatitis. Issue 4 (24th March 2018) - Patel, Devika; Levoska, Melissa; Shwayder, Tor
Abstract: Atopic dermatitis is a chronic, pruritic inflammatory disease that often disrupts sleep in severely affected children, but there are limited studies to guide clinical management of these sleep problems. Disease control is crucial in improving sleep, but additional sleep aids may sometimes be helpful in decreasing scratching during the night. This review discusses the benefits and limitations of potential therapeutic agents available to manage sleep disturbances in children with atopic dermatitis.